Identification of Symptomatic Carotid Artery Plaque: A Three-Item Scale Combined Angiography With Optical Coherence Tomography - Yang, Qingwen; Guo, Hongquan; Shi, Xuan; Xu, Xiaohui; Zha, Mingming; Cai, Haodi; Yang, Dahong; Huang, Feihong; Zhang, Xiaohao; Lv, Qiushi; Liu, Rui; Liu, Xinfeng (Frontiers in Neuroscience, 2021)
Introduction: Symptomatic carotid disease conveys a high risk of recurrent stroke. Plaque morphology and specific plaque characteristics are associated with the risk of stroke. This study aimed to evaluate the detailed plaque features of angiographical irregular plaque by optical coherence tomography (OCT) and develop a simple scale combining clinical indicators, digital subtraction angiography (DSA), and OCT imaging markers to identify symptomatic carotid plaque. Methods: Carotid plaques from consecutive patients who underwent carotid OCT imaging between June 2017 to June 2021 were evaluated. Clinical characteristics, DSA, and OCT data were compared between the symptomatic and the asymptomatic group. The association between plaque surface morphology detected by DSA and plaque characteristics evaluated by OCT was analyzed. Logistic regression was performed to identify the factors associated with symptomatic carotid plaque and to develop a scale. The area under the receiver operating characteristic curve (AUC) was used to evaluate the performance of the scale. Results: A total of 90 carotid plaques from 90 patients were included (symptomatic 35.6%, asymptomatic 64.4%). Irregular carotid plaque observed on DSA was more prone to be lipid-rich (OR, 4.096; 95% CI, 1.250 to 13.423; P = 0.020) and rupture (OR, 15.862; 95% CI, 4.598 to 54.719; P < 0.001). The three-item scale of symptomatic carotid plaque consisted of high-density lipoprotein cholesterol (HDL-C <0.925 mmol/L), angiographical irregular plaque, and white thrombus detected by OCT. The model had good discrimination (AUC, 0.768; 95% CI, 0.665 to 0.871). The optimal cut-off value of the scale was 1.5 points with 59.4% sensitivity and 84.5% specificity. Conclusions: Angiographical irregular carotid plaque had a high probability to be lipid-rich and rupture. The three-item scale comprised of dichotomous HDL-C, irregular plaque, and white thrombus may provide information to identify symptomatic carotid plaque.